PENGARUH RETURN ON EQUITY, NET INTERST MARGIN DAN BEBAN DAN PENDAPATAN OPERASIONAL TERHADAP HARGA SAHAM BANK RAKYAT INDONESIA TBK PERIODE 2013-2020 - Herlina; Rosdiana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
Investors in epidemic times should be more careful in investing in companies, therefore it is necessary to analyze the company's financial statements and conduct research using financial ratios to understand what ratios are and how much influence financial ratios have on stock changes. This is the effect of return on equity, net interst margin and operating expenses on operating income on the share price of Bank Rakyat Indonesia Tbk. This research method uses quantitative methods with single multiple linear regression analysis techniques and secondary data software sourced from the financial statements of Bank Rakyat Indonesia Tbk. The results of the t-test indicate that return on equity and Net interst margin have a positive and significant effect, while operating expenses and operating income have a negative and significant effect on stock prices, and the results of the F test show that return on equity, net interst margin and operating expenses operating income simultaneously have an effect positive and significant to stock prices.